Applying the Particle Swarm Optimization + Hill-climbing in the Flexible Job-Shop problem - Cardia, João Baptista; Kato, Edilson Reis Rodrigues (Journal on Advances in Theoretical and Applied Informatics; Vol 3 No 2 (2017): Journal on Advances in Theoretical and Applied InformaticsDO - 10.26729/jadi.v3i2.2430, 2017)
The Flexible Job-Shop problem is a very interesting and important problem. In this paper it is studied an approach of the PSO (Particle Swarm Optimization) in the Flexible Job-Shop problem, the studied and applied approach is derived from a Travelling Salesman Problem solution with a few minor alterations, trying to reach the optimum values discovered by a series of other works. It is used only PSO and not mixed with any other auxiliary meta-heuristic.